2023
DOI: 10.3390/foods12193669
|View full text |Cite
|
Sign up to set email alerts
|

Application Potential of Trichoderma in the Degradation of Phenolic Acid-Modified Chitosan

Maria Swiontek Brzezinska,
Beata Kaczmarek-Szczepańska,
Grażyna B. Dąbrowska
et al.

Abstract: The aim of the study was to determine the potential use of fungi of the genus Trichoderma for the degradation of phenolic acid-modified chitosan in compost. At the same time, the enzymatic activity in the compost was checked after the application of a preparation containing a suspension of the fungi Trichoderma (spores concentration 105/mL). The Trichoderma strains were characterized by high lipase and aminopeptidase activity, chitinase, and β-1,3-glucanases. T. atroviride TN1 and T. citrinoviride TN3 metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Our study has shown that only two of the fungi tested degraded the modified chitosan films. Our previous studies have also shown that not all fungi have the ability to degrade modified chitosan [ 16 ]. Trichoderma atroviride TN1 and Trichoderma citrinoviride TN3 best metabolized the chitosan films containing tannic acid, ferulic acid, and gallic acid.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study has shown that only two of the fungi tested degraded the modified chitosan films. Our previous studies have also shown that not all fungi have the ability to degrade modified chitosan [ 16 ]. Trichoderma atroviride TN1 and Trichoderma citrinoviride TN3 best metabolized the chitosan films containing tannic acid, ferulic acid, and gallic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Biological oxygen demand (BOD) is a measure of the biodegradation of polymers in the natural environment [ 27 ]. The biodegradation of the chitosan films in the soil after the application of Trichoderma strains was determined using the OxiTop system [ 16 ], according to the modified procedure described previously. One hundred grams of soil was transferred to an OxiTop system jar, chitosan film fragments (2 cm × 2 cm) were added and inoculated with fungal spores (1 mL spores, 10 5 CFU/mL).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations